Relationships between intellectual styles and academic achievement of Malaysian secondary school students - Damavandi, Alireza Jilardi (2012)
The present study aims to investigate the impact of Thinking and Learning styles on Academic achievement of secondary school students in Malaysia. This study attempts to identify the Thinking styles and Learning abilities that contribute to the variations in Academic achievement. The Kolb Learning Style Inventory (1999) and the Thinking Styles Inventory (TSI, Sternberg, Wagner, and Zhang, 2007) were administered in nine government schools in Kuala Lumpur. Mean scores of the students in five main subjects, namely English, science, mathematics, history and geography, were collected and the mean was calculated as academic achievement of the students. A total of 421 Grade 10 (form four) students was randomly selected as sample of this study. Results of the analyses of variance show no statistically significant difference in academic achievement of Malaysian secondary school students for the five dimensions (Function, Forms, Levels, Scopes and Leanings) of thinking styles. The results of regression analysis in indicated that Active Experimentation, Reflective Observation, Conservative and Oligarchic styles contribute significantly to the variations in the academic achievement; F (17, 394) = 2.798, p < .05. The findings add understanding on the intellectual styles of Malaysian secondary school students. Analaysing the contribution of intellectual styles towards subject-by-subject academic achievement indicated that six variables among the intellectual styles significantly predicted academic achievement results in five main subjects. These intellectual styles were Judicial, Anarchic, Oligarchic, Conservative, Active Experimentation, and Reflective Observation. Of these styles, Active Experimentation always positively predicts academic achievement in different subjects, while the Conservative style always negatively predicts academic achievement. The Judicial style significantly predicted students' academic achievements in mathematics and geography. Reflective Observation was among the predictors in English, history and geography. Finally, the Oligarchic and Anarchic styles significantly contributed to students' achievement in geography. The unique contributions of the intellectual styles to academic achievement in these five main subjects ranged from 7% to 10%. This finding not only indicates that intellectual styles play an important role in students' academic achievements in these subjects; it can also be interpreted that, in Malaysia, the use of these styles in dealing with these subjects tended to be rewarded academically. The findings of this study helped to extend knowledge in the profiling of intellectual styles in the Malaysian context. Furthermore, in order to assess Malaysian students’ thinking and learning styles, the translated thinking styles inventory (Sternberg, et al.,2007) and Kolb’s learning styles inventory (Kolb, 1999) can be used. As intellectual styles are important contributors to academic achievement, a clearer understanding of the role of each style can help teachers to be more effective in helping students to learn efficiently. In the current study, some recommendations are discussed for educational policy makers, teachers and researchers.